Housing Finance in India : A Comparative Study of Public and Private Sector Banks - Garg, Shiv Kumar; Kumar, Gajendra (Journal of Commerce and Trade, 2014)
Housing or shelter is the basic need of human being. This is accepted by the civilized society. Housing is an enigma to the developing countries; it is simultaneously the hardest problem to solvethe social housing schemes. Though shelter was enshrined as a fundamental right in the constitution, housing did not get the attention it reserved. In the light of bank reforms and government encouraged banking sectors to identify housing finance sector and its importance in lending. After 1990s all public sector banks were struggling with NPA problem. The housing shortage is increasing day by day as a proportion to the massive increase in population. Today, there are more than 350 housing finance companies registered with the registrar of companies of these 29 have been approved by NHB for financial assistance. Housing finance sector is fastest growing segment of the retail financing sector with a slew of tax breaks and sharp cut in of cost of owing housing, buying a house is easier. The agencies of public sector housing finance companies, Private sector housing companies and banks are competitors in housing finance market. Every citizen of the country dreams of having his own house. It is the bounden duty of the government to provide house to the houseless. Considering the paramount importance of housing, government no doubt considered.